2021
DOI: 10.3390/ijms222313094
|View full text |Cite
|
Sign up to set email alerts
|

Palm Oil-Rich Diet Affects Murine Liver Proteome and S-Palmitoylome

Abstract: Palmitic acid (C16:0) is the most abundant saturated fatty acid in animals serving as a substrate in synthesis and β-oxidation of other lipids, and in the modification of proteins called palmitoylation. The influence of dietary palmitic acid on protein S-palmitoylation remains largely unknown. In this study we performed high-throughput proteomic analyses of a membrane-enriched fraction of murine liver to examine the influence of a palm oil-rich diet (HPD) on S-palmitoylation of proteins. HPD feeding for 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The acyl-biotin exchange technique was applied to detect S -palmitoylation of DGKε essentially as described previously (36), with minor modifications. In brief, HEK293 cells were lysed in 500 μl of 150 mM NaCl, 5 mM EDTA, 1.7% Triton X-100, 4% SDS, cOmplete protease inhibitor cocktail, 2 mM PMSF, 250 U/ml Benzonase Nuclease, 50 mM Tris, pH 7.2, for 15 min at 37°C with shaking, followed by sonication for 60 s (0.3 cycle; amplitude 33%; UP200S Hielscher sonifier).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acyl-biotin exchange technique was applied to detect S -palmitoylation of DGKε essentially as described previously (36), with minor modifications. In brief, HEK293 cells were lysed in 500 μl of 150 mM NaCl, 5 mM EDTA, 1.7% Triton X-100, 4% SDS, cOmplete protease inhibitor cocktail, 2 mM PMSF, 250 U/ml Benzonase Nuclease, 50 mM Tris, pH 7.2, for 15 min at 37°C with shaking, followed by sonication for 60 s (0.3 cycle; amplitude 33%; UP200S Hielscher sonifier).…”
Section: Methodsmentioning
confidence: 99%
“…The acyl-biotin exchange technique was applied to detect S-palmitoylation of DGKε essentially as described previously (36), with minor modifications. In brief, HEK293 cells were lysed in 500 μl of 150 mM NaCl, 5…”
Section: Acyl-biotin Exchangementioning
confidence: 99%
“…Besides using enzyme modulators, dietary palmitate impacts the palmitoylation status of proteins. For instance, a palm oil-rich diet leads to accumulation of palmitate in membrane-enriched fractions of murine livers, as well as altered S-palmitoylation of proteins involved in the metabolism of fatty acids and cholesterol, such as fatty acid synthase, fatty acid elongase 2, stearoyl-CoA desaturase-1, CD36, and lanosterol synthase [122]. Similarly, several studies found that a high-fat diet, mainly enriched in animal fats, alters the S-palmitoylation of numerous proteins in peripheral organs and the central nervous systems, including but not limited to CD36 and the GluA1 subunit of the AMPA receptor [46,[123][124][125].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…The proteins involved in promoting various PTMs exist in several subcellular organelles, including the cytoplasm [ 39 ], ER [ 40 , 41 ], mitochondria [ 42 ], and nucleus [ 43 ]; PTMs may also be observed in the proteomes of the liver [ 37 , 44 47 ], gut [ 7 ], and other peripheral tissues [ 29 ]. PTMs found in liver diseases include protein acetylation [ 37 , 42 , 48 ], nitration [ 10 , 26 , 37 , 49 53 ], S -nitrosylation [ 49 , 54 , 55 ], oxidation [ 37 ], phosphorylation [ 26 , 56 , 57 ], succinylation [ 58 ], ADP-ribosylation [ 44 ], ubiquitination [ 37 , 59 ], SUMOylation [ 60 65 ], carbonylation [ 66 68 ], S -palmitoylation [ 45 47 , 69 ], glycosylation [ 7 , 37 , 70 , 71 ], protein adducts of aldehyde (i.e., acetaldehydes) [ 9 , 72 ], lipid peroxidation products (LPOs), and advanced glycation end products (AGEs) [ 6 , 66 , 74 79 ]. Several studies detail that specific PTMs correlate with exposures to excessive alcohol [ 80 , 81 ], CCl 4 [ 7 , 56 ], acetaminophen (APAP) [ 53 , 82 ], 3,4-methylenedioxymethamphetamine (MDMA, Ecstasy) [ 39 ], or fructose [ 51 ].…”
Section: Introductionmentioning
confidence: 99%